THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES AND CIVIL SOCIETY IN THE DEVELOPMENT OF LOCAL SELF-GOVERNMENT - ERYOMKA, Danylo; TABATSKYI, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article explores the role of information and communication technologies (ICT) in fostering effective, transparent, and accountable local self-government, with a strong emphasis on citizen participation. ICT has become an indispensable element in modern society, driving not only scientific and technological progress, but also democratic development. As civil society organizations and active citizens increasingly participate in local decision-making processes, ICT provides them with powerful tools for effective communication, mobilization, and influencing government decisions. The authors believe that the successful implementation of ICT in local self-government is crucial for sustainable development of Ukrainian communities and building trust between citizens and local authorities. The article further emphasizes the importance of e-governance as a powerful tool for fostering government transparency, transforming the interaction between citizens, businesses, and authorities. E-governance facilitates access to public information, empowers citizens to participate in shaping and implementing government decisions, and improves the quality of public services. The article also explores the impact of decentralization reforms on the evolving relationship between the government and the public. It argues that decentralization has shifted from a centralized system to a more flexible approach that considers the needs of communities. Simultaneously, advancements in ICT and its integration into public administration have made public services more accessible and convenient for citizens. The paper analyzes the two primary communication systems employed in Ukrainian government-civil society interactions: internal and external communication. It examines the advantages and challenges of digital transformation, explores models of collaboration between government bodies and civil society organizations, and highlights best practices for leveraging information technology to enhance local governance.